2003
DOI: 10.1152/ajpregu.00319.2002
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminoimidazole-4-carboxamide 1-β-d-ribofuranoside (AICAR) stimulates myocardial glycogenolysis by allosteric mechanisms

Abstract: We tested the hypothesis that activation of AMP-activated protein kinase (AMPK) promotes myocardial glycogenolysis by decreasing glycogen synthase (GS) and/or increasing glycogen phosphorylase (GP) activities. Isolated working hearts from halothane-anesthetized male Sprague-Dawley rats perfused in the absence or presence of 0.8 or 1.2 mM 5-aminoimidazole-4-carboxamide 1-β-d-ribofuranoside (AICAR), an adenosine analog and cell-permeable activator of AMPK, were studied. Glycogen degradation was increased by AICA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
116
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 49 publications
6
116
0
1
Order By: Relevance
“…1A). These results are consistent with several studies that have reported that phosphorylation of ACC is a sensitive marker of AMPK activity, often more sensitive even than increased levels of phosphoThr172-AMPK [29][30][31][32][33], and verify that phenformin treatment activated AMPK in differentiated hippocampal neurons.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphorsupporting
confidence: 93%
See 1 more Smart Citation
“…1A). These results are consistent with several studies that have reported that phosphorylation of ACC is a sensitive marker of AMPK activity, often more sensitive even than increased levels of phosphoThr172-AMPK [29][30][31][32][33], and verify that phenformin treatment activated AMPK in differentiated hippocampal neurons.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphorsupporting
confidence: 93%
“…Treatment with 10 mM phenformin caused a rapid, time-dependent increase in the phosphorylation of Ser79-ACC (Fig. 1A), a well-characterized substrate of AMPK [28] that is widely used as a detector of AMPK activation [29][30][31][32][33]. The phenformin-induced increase in phospho-Ser79-ACC was evident within 10 min of treatment and was maintained for 120 min.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphormentioning
confidence: 96%
“…However, further AMPK activation through acute AICAR stimulation resulted in a decrease in glycogen levels in myotubes from control and R225W carriers. While this reduction in glycogen content following acute AICAR treatment may have resulted from the phosphorylation of glycogen synthase kinase by AMPK, it may also be the result of allosteric activation of glycogen phosphorylase by AICAR [26,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AICAR is not completely specific for AMPK because ZMP regulates other AMP-sensitive enzymes such as fructose-1,6-bisphosphates (32) and muscle glycogen phosphorylase (33). Given the nonspecificity of AICAR to AMPK activation and the inconsistent findings discussed above, it is important to use an animal model in which AMPK activity is eliminated to determine the role of AMPK in insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%